TOURISM APPROACH IN GENTRICOLOGY: PENDEKATAN KEPARIWISATAAN DALAM GENTRIKOLOGI - Fendy E.W. Parengkuan; Dwianita Conny Palar (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Gentrification is a social phenomenon that involves regional transformation due to changes in social, economic, and cultural structures. This article discusses the relationship between gentrification and tourism through a gentricological approach, focusing on how the development of new areas due to gentrification contributes to the tourism potential in Indonesia. This research highlights the multifaceted role, ranging from government policies, business expansion, to socio-cultural impacts in gentrified areas. Various examples of regions such as Cilegon, Tanjung Bunga, Batam, and Tomohon were analyzed to identify the dynamics between indigenous and immigrant populations and their influence on local tourism activities. The results of the study show that gentrification can support the development of tourism through the emergence of new attractions, infrastructure improvements, and cultural diversification, although on the other hand it has the potential to cause social and economic inequality. These findings underscore the importance of careful and inclusive planning in the gentrification process so that the positive impact on the tourism sector can be maximized without neglecting the social sustainability aspect.